(untitled) (LEARNing Landscapes, 2023)
When trying to promote empathy, it is not sufficient to merely learn about other people and cultures if we seek to understand them better (Case, 1993). As a language arts teacher and researcher, the author sought to explore the potential for multicultural literature to expand adolescent learners’ worldviews and shape their perceptions as global citizensthrough classroom inquiry. This doctoral research features the case study of her Grade 8 class. Findings revealed that through narrative imagination (Nussbaum, 1997), learners’ experiences led to emerging themes of empathy, insight, and agency. This article focuses on the most prominent of these themes: empathy.